2017
DOI: 10.1177/1049731517699525
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial Investigating of a Single-Session Character-Strength-Based Cognitive Intervention on Freshman’s Adaptability

Abstract: To investigate the efficiency of a single-session character-strength-based cognitive intervention on enhancing freshmen's adaptability. Method: A randomized trial, pretest, posttest, follow-up intervention was employed using repeated-measures analyses to evaluate the effect. This 90-min intervention contained four activities with 52 undergraduate freshmen (age 17-20) randomly assigned to the intervention and control group, 38 of whom completed all the programs (19 of each group). Results: Compared with the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 51 publications
(67 reference statements)
2
36
0
Order By: Relevance
“…WBT was used as the sequential treatment for CBT (Fava et al, 2011). Character strengths could also be fused with CBT, which showed reliable efficacy in promoting mental health and well-being (Duan & Bu, 2019; Duan et al, 2019).…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
See 3 more Smart Citations
“…WBT was used as the sequential treatment for CBT (Fava et al, 2011). Character strengths could also be fused with CBT, which showed reliable efficacy in promoting mental health and well-being (Duan & Bu, 2019; Duan et al, 2019).…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
“…According to our previous experiences (Duan & Bu, 2019; Duan et al, 2019), we believe that combining strength-based strategies with the traditional WBT is reasonable to construct an SFI. For example, the character strength–based cognitive intervention (SCI; Duan & Bu, 2019; Duan et al, 2019) equips the existing CBT model with character strengths (i.e., positive personal assets; Peterson & Seligman, 2004) by conducting two successive intervention sections, that is, cognition (which focuses on the awareness and exploration of an individual’s signature strengths) and behavioral (which focuses on the application of an individual’s signature strengths) sections. The effectiveness of SCI in promoting well-being and alleviating negative emotions has been repetitively shown in existing literature (Duan & Bu, 2019; Duan et al, 2019).…”
Section: Sfi Developmentmentioning
confidence: 92%
See 2 more Smart Citations
“…The eight remaining papers focused on a part of the positive education model. Research has shown that character strengths are linked to positive youth development (Park et al, 2004;Duan et al, 2015) and numerous valued outcomes (e.g., decreases in depression, increase in life satisfaction, and achievement) (Duan and Bu, 2017;Schutte and Malouff, 2019). In line with previous research, Zhang and Chen discovered that certain character strengths, namely, hope, curiosity, zest, perseverance, and love bear the strongest correlations with subjective wellbeing.…”
Section: Approaches To Positive School Educationmentioning
confidence: 59%